The Role of Trabectedin in Soft Tissue Sarcoma - Nakamura, Tomoki; Sudo, Akihiro (Frontiers in Pharmacology, 2022)
Background: Systemic chemotherapy for advanced disease is another therapeutic option in the management of metastases in soft tissue sarcoma (STS). Doxorubicin either alone or in combination with ifosfamide has been used as first-line chemotherapy. Furthermore, in the past decade, new drugs have been shown to be effective in the treatment of advanced STS after the failure of first-line anthracycline-based chemotherapy: trabectedin, pazopanib and eribulin. However, the appropriate usage of these agents has not been established. Methods: We summarized clinical trials of trabectedin focusing on the efficacy and toxicity of trabectedin in the treatment of STS. Results: Trabectedin can be administered safely and effectively to the patients with advanced STS at second line setting or later. Although trabectedin may be effective as first-line treatment in selected patients, anthracycline-based chemotherapy should be recommended because no regimen in addition to trabectedin has proved to be unequivocally superior to doxorubicin as the first-line treatment for locally advanced or metastatic STS. Nucleotide excision repair (NER) and homologous recombination (HRe) repair may be of particular importance as efficacy of trabectedin. Conclusion: Trabectedin has shown a favorable toxicity profile and is an alternative therapeutic option in patients with advanced STS.